Nutritional outcomes in patients undergoing transoral robotic surgery for head and neck cancers compared to conventional open surgery. Systematic review. Issue 1 (1st November 2021) - Anakapu, Kimberley; Wilson, Michael; Findlay, Merran; Brown, Teresa; Bauer, Judith
Abstract: This systematic review examined nutritional outcomes in patients undergoing transoral robotic surgery (TORS), compared to open surgery (OS) for head and neck cancer. PUBMED, CINAHL, and Web of Science were systematically reviewed. Target nutritional outcomes included: weight, nutritional status, use of enteral feeding, swallowing function/ability, and time to oral diet. Risk of bias was assessed using the risk of bias in non‐randomized studies tool, and certainty of evidence was assessed using grading of recommendations, assessment, development, and evaluation (GRADE). Eight studies were included (total n  = 608). Compared to OS, TORS probably reduces short‐ and long‐term enteral feeding use or duration (GRADE "moderate" certainty), may reduce time to full swallow ability (GRADE "low" certainty), but it remains uncertain whether TORS reduces long‐term patient reported swallowing function or time to oral feeding (GRADE "very‐low" certainty). No studies examined nutritional status or weight. There is limited body of evidence examining nutrition outcomes following TORS. Further studies are warranted, which may improve the certainty of evidence and assist in determining the optimal nutrition care for these patients.